Development of an Augmented Reality-Based Body Parts Concept Book for Early Childhood - Tria Meidiana Tria; Umar bin Abd Aziz; Safrul Muluk; Dewi Fitriani (Indonesian Journal of Early Childhood Educational Research (IJECER), 2026)
Introducing body parts is an important basic concept for early childhood; however, the available learning media are still dominated by two-dimensional images that are less interactive. This study aimed to develop and examine the feasibility of an Augmented Reality (AR)-based body parts concept book integrating three-dimensional (3D) object visualization and interactive audio in accordance with the learning characteristics of early childhood. The novelty of this study lies in the integration of marker-based AR, full-body 3D visualizations, and learning activities within a single concept book specifically designed for children aged 4–5 years. This study employed a Research and Development (R&D) method using the ADDIE model. The research subjects consisted of 17 children aged 4–5 years at TKIT Baitushalihin Banda Aceh. The research instruments included expert validation sheets (material and media experts) and children’s response observation sheets. Data were analyzed using quantitative descriptive percentage analysis and qualitative descriptive analysis. The results showed that the validation by material experts and media experts reached 100% (very feasiable). Children’s responses in the small-group trial (n=8) obtained a percentage of 91.25% (very feasiable), while the large-group trial (n=17) obtained 80.88% (feasiable). These findings indicate that AR media can support children’s attention, engagement, and understanding of body parts concepts through more concrete visual and auditory experiences. Therefore, the developed media is appropriate to be used as an innovative alternative in early childhood learning, although further effectiveness testing using an experimental design is still needed.